Розробка нечіткої системи прогнозування витрат палива автомобіля на основі даних про стиль водіння та параметри дороги - Задрикін, А. О. (ХНУРЕ, 2023)
This paper proposes the development of a fuzzy system for predicting fuel consumption of a vehicle based on driver's driving style and road parameters. The proposed system uses fuzzy logic to analyze input variables such as vehicle speed, acceleration, road gradient, and road surface condition to obtain an accurate estimate of fuel consumption To develop the system, a dataset on driving styles and corresponding fuel consumption values was collected from the fleet of vehicles. The dataset was processed and analyzed to extract relevant features, which were then used to develop and train a fuzzy system. Overall, this paper demonstrates the potential of using fuzzy logic in developing predictive models for complex systems such as vehicle fuel consumption.
Keywords: витрати палива; нечітка система передбачення; нечітка логіка